The Influence of Climate on Seepage from Mine Waste Storages During Deposition and Post-Closure - Williams, D.J. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
Surface mine waste storages have the potential to generate contaminated seepage. While exposure to oxygen and the presence of high salinity are primarily responsible for the production of contaminants, the emergence of seepage from stored mine wastes is primarily dependent on the moisture state of the wastes on deposition, the geometry of the waste storage, and the duration of exposure to the climatic setting. Seepage rates are also affected by the extent to which the mine waste storage facilities are lined, whether naturally or by design, and by the effectiveness of any cover placed by way of rehabilitation. During the operation of a surface waste rock dump, oxygen is readily available, and the dump will wet up with rainfall at a rate dependent upon the amount and intensity of rainfall, the height of the dump, and the particle size distribution of the waste rock. On closure of a surface waste rock dump, some attempt may be made to limit both the ingress of oxygen and the net percolation of rainfall infiltration, through the placement of a suitable cover system over the dump. During the operation of a surface tailings storage facility, seepage will occur due to the large volume of water discharged with the tailings, although the ingress of oxygen into the tailings may be limited by their generally high degree of saturation. On closure of a surface tailings storage facility, seepage will diminish as the tailings drain down and will become controlled by rainfall, while desiccation of the tailings will allow greater ingress of oxygen. Some attempt may be made to limit both the ingress of oxygen and the net percolation of rainfall infiltration through the placement of a suitable cover system over the tailings, and the management of rainfall runoff. The paper describes the range of climatic regimes in which mines are located, ranging from arid, net evaporative climates to wet tropical, net infiltrative climates. It goes on to describe the superposition of the water balance of surface mine waste storages on these climatic regimes, both during their operation and post-closure, including the effectiveness of lining and cover systems in mitigating potentially contaminated seepage.